2020
DOI: 10.37201/req/067.2019
|View full text |Cite
|
Sign up to set email alerts
|

Micafungin as antifungal prophylaxis in non-transplanted haemotological patients

Abstract: Micafungina como profilaxis antifúngica en pacientes hematológicos no trasplantados RESUMENIntroducción. Las infecciones fúngicas son una importante causa de morbilidad y mortalidad en los pacientes hematológicos. Estas infecciones son principalmente debidas a Candida spp.y Aspergillus spp. La mortalidad debida a estas infecciones es alta, pero ha descendido a lo largo de las últimas series gracias a los mejores agentes antifúngicos. Las equinocandinas son, in vitro, muy activas contra Candida y Aspergillus sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…While all three echinocandins have been studied in various patient populations ( 13 , 43 48 ), only micafungin is indicated for use as antifungal prophylaxis, specifically, of Candida infections in adult and pediatric patients undergoing hematopoietic stem cell transplantation ( 12 , 49 , 50 ). In a retrospective study in patients with hematological disease who received antifungal prophylaxis, micafungin was selected in 26% of 104 cases for safety- or tolerability-related reasons (e.g., liver dysfunctions, severe mucositis, DDIs of other antifungals, and long QT syndrome) ( 51 ). The safety of rezafungin is consistent with that of the echinocandin class, as observed in the phase 2 STRIVE trial of once-weekly rezafungin compared to caspofungin in the treatment of candidemia and invasive candidiasis ( 35 , 52 ) and in phase 1 trials that confirmed rezafungin lack of effect on the QT interval and low DDI potential ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…While all three echinocandins have been studied in various patient populations ( 13 , 43 48 ), only micafungin is indicated for use as antifungal prophylaxis, specifically, of Candida infections in adult and pediatric patients undergoing hematopoietic stem cell transplantation ( 12 , 49 , 50 ). In a retrospective study in patients with hematological disease who received antifungal prophylaxis, micafungin was selected in 26% of 104 cases for safety- or tolerability-related reasons (e.g., liver dysfunctions, severe mucositis, DDIs of other antifungals, and long QT syndrome) ( 51 ). The safety of rezafungin is consistent with that of the echinocandin class, as observed in the phase 2 STRIVE trial of once-weekly rezafungin compared to caspofungin in the treatment of candidemia and invasive candidiasis ( 35 , 52 ) and in phase 1 trials that confirmed rezafungin lack of effect on the QT interval and low DDI potential ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%